2017
DOI: 10.21037/jtd.2017.03.22
|View full text |Cite
|
Sign up to set email alerts
|

Performance in the shuttle walk test is associated with cardiopulmonary complications after lung resections

Abstract: Background:The current functional guidelines recommend the shuttle walk test (SWT) as an initial screening tool to identify candidates for lung resection without requiring cardiopulmonary exercise testing.This study aims to: (I) assess the use of the SWT in predicting postoperative cardiopulmonary complications;and (II) determine whether the recommended 400 m cut-off is an appropriate distance. Methods:We retrospectively analysed 101 patients that had performed a SWT prior to surgery. Univariate and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…All patients were selected for pulmonary resection according to current functional guidelines and after discussion during a multidisciplinary tumour board meeting [13]. A preoperative symptom-limited CPET on an electronically braked cycle ergometer was performed to detect the deficit in their oxygen transport system when the postoperative predicted (ppo) FEV1 or ppoDLCO (or both) are <30%, or if the distance walked during shuttle walk test was shorter than 400 meters, according to the locally 5 5 accepted guidelines [1,14].…”
Section: Methodsmentioning
confidence: 99%
“…All patients were selected for pulmonary resection according to current functional guidelines and after discussion during a multidisciplinary tumour board meeting [13]. A preoperative symptom-limited CPET on an electronically braked cycle ergometer was performed to detect the deficit in their oxygen transport system when the postoperative predicted (ppo) FEV1 or ppoDLCO (or both) are <30%, or if the distance walked during shuttle walk test was shorter than 400 meters, according to the locally 5 5 accepted guidelines [1,14].…”
Section: Methodsmentioning
confidence: 99%
“…Three studies (Erdoǧan et al, 2013;Win et al, 2004;Fennelly et al, 2016) investigated the association between preoperative iSWT performance and postoperative complications. One study reported that oxygen desaturation ≥4% during the iSWT, and distance walked <400 m were associated with a higher risk of postoperative complications (Fennelly et al, 2016). In two studies, no associations were found between outcomes of the preoperative iSWT and postoperative complications (Erdoǧan et al, 2013;Win et al, 2004).…”
Section: Incremental Shuttle Walk Testmentioning
confidence: 99%
“…Pre-operatively in thoracic surgery, this manifests through several objective functional tests which are performed in addition to pulmonary function tests, (particularly in those with poor or borderline pulmonary function tests) to augment the decision-making process in terms of assessing suitability for surgery. These functional tests include the six-minute walk, the shuttle test and the cardiopulmonary exercise test (CPET) and have been proven to correlate well with postoperative outcomes (27)(28)(29)(30).…”
Section: Pulmonary Function Tests and Objective Functional Testingmentioning
confidence: 99%